Emotional and Spiritual Intelligence of Future Leaders: Challenges for Education - Joanna Samul (Education Sciences, 2020)
The study was focused on understanding emotional and spiritual intelligence, and leadership linkages. The aim of the study was to explore the relationship between emotional and spiritual intelligence and self-leadership skills of university students in the fields of management, as potential future leaders. The data were collected using three scales: Emotional Intelligence Scale (WLEIS), Spiritual Intelligence Inventory (SISRI-24), and Self-Leadership questionnaire. The study was conducted among 190 university students. The results obtained show that there are connections between emotional and spiritual intelligence and self-leadership. The study may be a good starting point for further research in this field and lead to reflection about spiritual knowledge on the leadership education program.